Investigating the impact of vessel geometry on cerebral aneurysm formation using multi-phase blood flow models - Lampropoulos, Dimitrios S.; Hadjinicolaou, Maria (Computers & mathematics with applications (1987), 2024)
Cerebral aneurysms represent a life-threatening condition associated with considerable morbidity and mortality rates. The formation of cerebral aneurysms is influenced by various factors, including vessel geometry, blood flow characteristics, and hemodynamic forces. In this study, we investigate the impact of vessel geometry on the formation of cerebral aneurysms utilizing computational fluid dynamics (CFD) simulations for multi-phase blood flow models. More precisely, we employ the Finite Volume Method to numerically solve the Navier-Stokes equations for simulating blood flow. To accurately capture the intricate nature of blood behavior, we utilize a multiphase blood flow model, as blood consists of red blood cells, white blood cells, and platelets suspended in the blood plasma. Our results demonstrate that the local curvature of the vessel has a pronounced effect on the blood flow patterns and hemodynamic forces within the vessel. Specifically, our simulations indicate that an increase in vessel curvature can lead to the formation of regions of high stress and flow stagnation, both of which are known to be associated with an increased risk of aneurysm formation. The current study provides significant insights into the impact of vessel geometry on the formation of cerebral aneurysms. The obtained results may aid in designing treatment and preventive strategies for cerebral aneurysms, while also contributing to the existing body of knowledge on the subject. Additionally, the approach developed in this study can be applied to investigate various other vascular pathologies, including arterial stenosis and atherosclerosis. •Vessel geometry, especially curvature, significantly influences blood flow and hemodynamic stress.•Increased vessel curvature leads to high-stress areas and flow stagnation, precursors to aneurysm formation.•Our findings enhance understanding of vessel geometry's role in cerebral aneurysm development.•This research aids in designing effective aneurysm treatment and prevention strategies.•Our approach may apply to studying other vascular diseases, including stenosis and atherosclerosis.